Au133(SPh‑tBu)52 Nanomolecules: X‑ray Crystallography, Optical, Electrochemical, and Theoretical Analysis - Dass, Amala; Theivendran, Shevanuja; Nimmala, Praneeth Reddy; Kumara, Chanaka; Jupally, Vijay Reddy; Fortunelli, Alessandro; Sementa, Luca; Barcaro, Giovanni; Zuo, Xiaobing; Noll, Bruce C (Journal of the American Chemical Society, 2015)
Crystal structure determination has revolutionized modern science in biology, chemistry, and physics. However, the difficulty in obtaining periodic crystal lattices which are needed for X-ray crystal analysis has hindered the determination of atomic structure in nanomaterials, known as the “nanostructure problem”. Here, by using rigid and bulky ligands, we have overcome this limitation and successfully solved the X-ray crystallographic structure of the largest reported thiolated gold nanomolecule, Au133S52. The total composition, Au133(SPh-tBu)52, was verified using high resolution electrospray ionization mass spectrometry (ESI-MS). The experimental and simulated optical spectra show an emergent surface plasmon resonance that is more pronounced than in the slightly larger Au144(SCH2CH2Ph)60. Theoretical analysis indicates that the presence of rigid and bulky ligands is the key to the successful crystal formation.